Restricted triangulation on circulant graphs - Ali, Niran Abbas; Kilicman, Adem; Trao, Hazim Michman (De Gruyter, 2018)
The restricted triangulation existence problem on a given graph decides whether there exists a triangulation on the graph’s vertex set that is restricted with respect to its edge set. Let G = C ( n , S ) be a circulant graph on n vertices with jump value set S . We consider the restricted triangulation existence problem for G . We determine necessary and sufficient conditions on S for which G admitting a restricted triangulation. We characterize a set of jump values S ( n ) that has the smallest cardinality with C ( n , S ( n )) admits a restricted triangulation. We present the measure of non-triangulability of K n − G for a given G .